FENOMOLOGI PUASA SENIN KAMIS DI SEKOLAH TINGGI DIRASAT ISLAMIYAH IMAM SYAFI'I JEMBER - Nandang Husni Azizi; Izzaturrahman, Fauzi; Muhammad Yassir (Al-Majaalis : Jurnal Dirasat Islamiyah, 2023)
Fasting is one of the obligations of one of the pillars of Islam for Muslims, namely to refrain from anything that breaks the fast. There are many types of sunnah fasting that the Prophet sallallaahu alaihi wasalam taught besides obligatory fasting in the month of Ramadan such as the fasting of David, Arafah, Asy Shura and so on including fasting on Mondays and Thursdays which are discussed in this article. The methodology used in this article is qualitative using a living hadith approach, namely a phenomenological study of hadith conducted by a group of people in a certain place. Dirasat Islamiyah High School is a tertiary institution that teaches religious knowledge and fundamental matters as well as detailed matters in religion based on justifiable arguments and understanding in accordance with the Ahlu Summah wal Jama'ah methodology both in terms of knowledge, practice and da'wah. There is an interesting phenomenon in that most of the students who study there practice fasting on Mondays and Thursdays. Many of them practice fasting on Mondays and Thursdays based on a hadith in this practice, but there are those whose fasts are due to encouragement from the surrounding environment. On average, they know the reasoning or foundation of a practice, even though some of them are motivated by worldly things, such as providing an iftar menu for every sunnah fast they practice. The core books in the field of hadith which mention the hadiths that can be the basis for fasting Monday and Thursday. Keywords: sunnah fasting, monday, thursday.